1994
DOI: 10.1148/radiology.191.1.8134583
|View full text |Cite
|
Sign up to set email alerts
|

Chest wall and mediastinal invasion by lung cancer: evaluation with multisection expiratory dynamic CT.

Abstract: Multisection ED CT may improve the accuracy of CT in prediction of chest wall or mediastinal invasion of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
8

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 0 publications
1
32
0
8
Order By: Relevance
“…As well as the technique of inducing artificial pneumothoraces as described earlier, dynamic expiratory multisection CT (viewed as a cine loop) has also been evaluated. In a study of 15 patients, this was found to be 100% accurate for chest wall and mediastinal fixation at pathological examination [100]. With conventional CT imaging, the only reliable criterion for establishing definite invasion is bony destruction with or without tumour mass extending between the ribs and into the chest wall ( fig.…”
Section: Tumour Statusmentioning
confidence: 98%
“…As well as the technique of inducing artificial pneumothoraces as described earlier, dynamic expiratory multisection CT (viewed as a cine loop) has also been evaluated. In a study of 15 patients, this was found to be 100% accurate for chest wall and mediastinal fixation at pathological examination [100]. With conventional CT imaging, the only reliable criterion for establishing definite invasion is bony destruction with or without tumour mass extending between the ribs and into the chest wall ( fig.…”
Section: Tumour Statusmentioning
confidence: 98%
“…In a similar fashion to MR, the evaluation then relies on coronal and sagittal images reconstructed from these data. Dynamic CT during a single expiratory manoeuvre over a time period of 10 s relies either on electron beam scanning (200 ms?image -1 , one image every second [40]), or on continuous data acquisition using spiral CT scanners (250-500 ms?image -1 ). Such expiratory dynamic CT was found to provide accurate information in all 15 patients studied [40] but only proved to be helpful for tumours located in the middle and lower lobes.…”
Section: T-stagingmentioning
confidence: 99%
“…Outros estudos utilizando TC com avaliação dinâmica do movimento respiratório, que observa a mudança relativa de localização entre o tumor pulmonar periférico e a parede durante a respiração, mostraram que a presença de tal deslocamento é um confiável indicador de ausência de invasão pleural parietal pelo tumor (12,13) .…”
Section: Avaliação Do Tumor Primário (Fator T)unclassified
“…Radiologia do câncer de pulmão massa adjacente à estrutura mediastinal, espessamento pleural ou pericárdico (10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Figura 1 -Imagem De Tc Obtida No Plano Axial Com 2mm De Colunclassified
See 1 more Smart Citation